PENERAPAN MODEL PEMBELAJARAN BERBALIK (RECIPROCAL TEACHING) DITINJAU DARI AKTIVITAS DAN HASIL BELAJAR SISWA - Vahlia, Ira; Sudarman, Satrio Wicaksono (UNIVERSITAS MUHAMMADIYAH METRO, 2015)
The aim of the research was to determine the effect of learning models on mathematics achievement viewed from the student activity. Many factors influence the results of student learning, including learning system used in presenting the subject matter inappropriate, as well as the lack of students understand the concepts being taught. Based on the results of the pre-survey, retrieved the data value of the Mid Semester Even-Numbered Years Lessons 2014/2015 that of the 23 students there are 13 students who are learning or mastery of 56,52%. It takes the efforts of teachers to choose the model of learning material appropriate to each lesson. For the average activity of students obtained an increase in the activity of learning from 52,42% on cycle I became 64,2%5 in cycle II. As for the student learning outcomes there is also increased, the average results of the learn cycle I is 63,54, while on cycle II increased to 70,65 and success of the student learning at the end of the cycle reaches 81,09. It was concluded that the reciprocal teaching model, can improve the learning results of activity and grade VIII SMP Negeri 4 Metro.